Financial Structures and Economic Outcomes : An Empirical Analysis - Gole, Tom (IMF Working Papers; Working Paper ;, 2013)
This paper investigates the potential relationships between financial structures and economic outcomes. The empirical results that withstand a battery of methods suggest that some financial intermediation structures are likely to be more closely related to positive economic outcomes than others. For instance, protective financial buffers within institutions have been associated with better economic performance, and a domestic financial system that is dominated by some types of nontraditional bank intermediation or that has a high proportion of foreign banks has in some cases been associated with adverse economic outcomes, especially during the financial crisis. The results also suggest that there may be trade-offs between beneficial effects on growth and stability of some financial structures. For example, the positive association of financial buffers with growth can diminish above a certain, relatively high, threshold-a too-safe system may limit the available funds for credit and hence growth.